THE PERFORMANCE OF THE LIBRARY OFFICE OF MAKASSAR CITY IN INCREASING PUBLIC READING INTEREST - Saguni, Dewi Sulfa; Widyawati, Widyawati; Yusuf , Nimrah Rahmayanti (Jurnal Administrasi Negara, 2023)
The lack of reading interest in society has an effect not only on the rise of illiteracy, but also on the state of education in the nation. Researchers in the disciplines of education and culture have conducted studies to solve the problem of low interest in reading and provide recommendations for government, community, and library participation. This study will respond by focusing on the government’s function as the entity responsible for boosting the public’s reading interest. This study aims to ascertain the extent to which the performance of the Makassar City Library Service affects the public’s enthusiasm for reading. To make it simpler to observe the effect of performance on reading interest, quantitative research methods were chosen. The respondents consisted of 46 employees and librarians actively involved in the implementation of the work programs of the Makassar City Library Service. The statistical analyses conducted with SPSS 26 revealed that the effect of the performance of the Makassar City Library Service on the increase of public interest in reading was only 15.6%, with a F count greater than F table 3.21. In six years, the reading interest has increased by 5.82 percent as a result of this factor. The performance of the Makassar City Library Service, which significantly contributes to a rise in public interest in reading, is dependent on the competencies and skills of its employees. The reading interest of the city of Makassar has increased as a result of indicators of community action to locate reading material. This is also inextricably linked to the performance of the Makassar City Library Service in supplying affordable reading materials.